The most beautiful bibles - Fingernagel, Andreas; Gastgeber, Christian (Taschen, 2008)
Covers examples from various epochs of the Middle Ages, presenting the Bible as it was visualized in both theological and historical contexts. This title describes each manuscript in detail and explores the evolution of the Bible as well as the medieval understanding of history that is inherent in these versions of the Bible.